Cyborg and the Future Man: Children’s Stories for Chinese Boy Readers - Runyuan Bai (Writing Chinese: A Journal of Contemporary Sinophone Literature)
This article examines how technological mastery addresses the boyhood crisis and advances national aspirations in Chinese children’s science fiction, with a focus on Yi Ping’s The Burning Planet. This paper argues that technological mastery is central to masculinity ideals in Chinese children’s science fiction, positioning boys' proficiency in science and technology as crucial to addressing the boyhood crisis and establishing China as a future leader in the global technological landscape. Using cyborg theory, Chinese masculinity studies, and Adorno’s cultural industry framework, this study explores how children’s literature constructs masculinity ideals while embedding nationalist ideologies. The discussion is constructed through three thematic lenses- the monster, the mirror, and the mastery. The ‘Monster’ lens highlights the protagonist’s transformation into a cyborg, representing both technological empowerment and the erosion of individuality under ideological control. The ‘Mirror’ lens reflects current societal anxieties about boys’ academic and physical inadequacies, situating these concerns within broader cultural and nationalistic aspirations of tomorrow. The ‘Mastery’ lens put technological proficiency as the proposed solution to these challenges, portraying boys as crucial agents in achieving China’s global leadership in technology and culture. The cyborg serves as a pivotal construct, intertwining evolving gender dynamics, societal expectations, and nationalist aspirations. It functions as both a reflection of and a response to social anxieties. This study positions the transformative role of technology in science fiction as a cultural mediator, demonstrating how ideological constructs and gender identities are negotiated through futuristic narratives in contemporary Chinese children’s literature.